Phenotype to Genotype: A Novel Case Presentation of CPT2 Deficiency Syndrome - Bhalla, Aradhana Aggarwal; Sinha, Raj Kumari; Thakur, Seema (Journal of Fetal Medicine, 2025)
Prenatal detection of recurrent structural anomalies presents complex challenges in fetal prognosis and genetic counseling. We report the case of a 25-year-old woman with three consecutive pregnancies affected by bilateral hyperechoic, enlarged fetal kidneys and associated anomalies. In the first pregnancy, anomaly scan at 18 + 6 weeks revealed enlarged hyperechoic kidneys, Dandy-Walker malformation, and echogenic bowel. The pregnancy was terminated; microarray analysis was normal. A year later, her second pregnancy showed similar renal findings along with enlarged lateral ventricles, absent cavum septum pellucidum, and microcephaly. Trio whole-exome sequencing identified compound heterozygous variants in the CPT2 gene in the fetus: c.28_29insAGCAAG and c.1891C > T. Both parents were found to be heterozygous carriers. In the third pregnancy, clinical exome sequencing was offered as prenatal testing despite a normal ultrasound. The fetus was initially reported as “affected” with the same compound heterozygous CPT2 variants. However, reanalysis by a clinical geneticist revealed that both variants were in cis configuration in the parents and fetus, indicating a carrier status rather than disease. This case underscores the importance of detailed variant interpretation, phase determination, and expert genetic counseling in managing suspected fetal CPT2 deficiency, especially in cases presenting with recurrent antenatal anomalies.
Keywords: CPT2 gene; fetal renal anomalies; prenatal diagnosis; compound heterozygosity; genetic counseling